2014
DOI: 10.1111/apt.12807
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: interactions between aspirin, and other nonsteroidal anti‐inflammatory drugs, and polymorphisms in relation to colorectal cancer

Abstract: BackgroundNonsteroidal anti-inflammatory drugs (NSAIDs) include aspirin (acetylsalicylic acid, ASA). Long-term use of NSAIDs has been associated with lowered risk of colorectal cancer (CRC), but the use is hampered by adverse effects. Also, the anti-carcinogenic effects of NSAIDs are incompletely understood. Understanding biological effects of NSAIDs may help developing new preventive medical strategies.AimTo identify gene–environment interactions between genetic variation and NSAID use in relation to risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 69 publications
(234 reference statements)
0
31
0
Order By: Relevance
“…Gene-environment interaction analyses may identify underlying biological pathways associated with effects of diet (46,47). Our analyses suggest that the meat carcinogenic pathway involves activation of TLR1 and TLR10 followed by activation of NF-ĸB-initiated transcription of inflammatory genes (Figure 1).…”
Section: Discussionmentioning
confidence: 91%
“…Gene-environment interaction analyses may identify underlying biological pathways associated with effects of diet (46,47). Our analyses suggest that the meat carcinogenic pathway involves activation of TLR1 and TLR10 followed by activation of NF-ĸB-initiated transcription of inflammatory genes (Figure 1).…”
Section: Discussionmentioning
confidence: 91%
“…There has been an increase in the incidence of CRC over the past few years due to demographical changes and the implementation of a Western lifestyle in developing countries (Andersen and Vogel, 2014). It is a multifactorial disease resulting from complex interactions between genetic, epigenetic, and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…DMH is metabolized in the liver to form azoxymethane and methylazoxymethanol which is further transported to the colon via bile or blood to generate its ultimate carcinogenic metabolite, diazonium ion, which elicits an oxidative stress by methylating biomolecules of colonic epithelial cells and leads to promutagenic events as a result of inflammation and tumor promotion. It is already reported that the overexpression of inducible nitric oxide synthase (i-NOS) and cyclooxygenase-2 (COX-2) is associated with colorectal cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“…Aspirin or acetylsalicylic acid is a drug in the salicylate family and of the class of NSAID. The epidemiological studies and clinical trials indicate that longterm use of Aspirin could possibly decrease the incidence of certain malignancies, including colorectal, oesophageal, breast, lung and bladder cancer [11][12][13]. However, long-term use of Aspirin is limited to gastric and renal toxicity [14].…”
Section: Introductionmentioning
confidence: 99%